The gene encoding Arabidopsis acyl-CoA-binding protein 3 is pathogen inducible and subject to circadian regulation - Zheng, Shu-Xiao; Xiao, Shi; Chye, Mee-Len (Journal of experimental botany, 2012)
In Arabidopsis thaliana, acyl-CoA-binding protein 3 ( ACBP3), one of six ACBPs, is unique in terms of the C-terminal location of its acyl-CoA-binding domain. It promotes autophagy-mediated leaf senescence and confers resistance to Pseudomonas syringae pv. tomato DC3000. To understand the regulation of ACBP3, a 1.7 kb 5'-flanking region of ACBP3 and its deletion derivatives were characterized using β-glucuronidase (GUS) fusions. A 374 bp minimal fragment (-151/+223) could drive GUS expression while a 1698 bp fragment (-1475/+223) conferred maximal activity. Further, histochemical analysis on transgenic Arabidopsis harbouring the largest (1698 bp) ACBP3pro::GUS fusion displayed ubiquitous expression in floral organs and vegetative tissues (vascular bundles of leaves and stems), consistent with previous results showing that extracellularly localized ACBP3 functions in plant defence. A 160 bp region (-434/-274) induced expression in extended darkness and caused down-regulation in extended light. Electrophoretic mobility shift assay (EMSA) and DNase I footprinting assay showed that the DNA-binding with one finger box (Dof-box, -341/-338) interacted specifically with leaf nuclear proteins from dark-treated Arabidopsis, while GT-1 (-406/-401) binds both dark- and light-treated Arabidopsis, suggesting that Dof and GT-1 motifs are required to mediate circadian regulation of ACBP3. Moreover, GUS staining and fluorometric measurements revealed that a 109 bp region (-543/-434) was responsive to phytohormones and pathogens. An S-box of AT-rich sequence (-516/-512) was identified to bind nuclear proteins from pathogen-infected Arabidopsis leaves, providing the basis for pathogen-inducible regulation of ACBP3 expression. Thus, three cis-responsive elements (Dof, GT-1, and the S-box) in the 5'-flanking region of ACBP3 are proven functional in the regulation of ACBP3.